A testbed for a magnetic refrigeration system at room temperature and its experimental evaluation. (1st August 2022) - Choi, Jongmin; Lee, Seungyeon; Kim, Min Soo
Highlights: A new testbed is developed for a reciprocating magnetic refrigeration system. The magnetic assembly enables both series and parallel AMR modes. A novel sequential flow controller simplifies the magnetic refrigeration system. Cartridge-type AMR is suggested for layering different magnetocaloric materials. 25.5 W/kg of the maximum specific cooling capacity was obtained in the testbed. Abstract: In this research, a new testbed for a magnetic refrigeration system (MR system) at room temperature is proposed. The testbed is characterized by a magnetic assembly for both series and parallel active magnetic regenerator (AMR) modes, a hydraulic system simplified by a novel sequential flow controller, and a cartridge-type AMR with an original design for mechanically packing magnetocaloric materials. To evaluate the testbed, experimental analysis was performed. Firstly, the magnetic assembly was measured that the maximum magnetic flux density was 0.921 T in the magnetization area and the minimum was 0.013 T in the demagnetization area. It was found that the sequential flow controller worked up to 0.63 Hz of the operating frequency. Moreover, the controller was validated to operate in both magnetic Brayton and hybrid Brayton-Ericsson refrigeration cycles with data on the mass flow rate of the heat transfer fluid. According to the performance test using 60.3 g of Gadolinium in the cartridge-type AMRs, the testbed achieved 5.9 K of maximum temperature span at 0.63 Hz of operating frequency and 0.52 of utilization factor in the parallel AMR mode without a thermal load in the hybrid cycle. In a load test, the system produced a maximum of 1.54 W of cooling capacity with 2.4 K of temperature span and 0.8 of coefficient of performance in the parallel AMR mode at 0.56 Hz of operating frequency and 0.75 of utilization factor during the hybrid cycle. Finally, the results state that the overlap of the higher and lower temperature cycles adversely influenced the temperature span in the series mode while the parallel mode contributed to a stable temperature span, especially in the thermal load condition.